2010
DOI: 10.1177/1046496410389493
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Group Attendance Using In-Session Behaviors

Abstract: A session-level analysis examines the relationship between intimate behaviors of an individual group member and of the other group members in a session, and individual group member attendance in the following session. Specifically, the model proposed by Kenny, Mannetti, Pierro, Livi, and Kashy (2002) for analyzing individual and group effects in small groups is used to examine session attendance in 575 group sessions for 30 group members in 5 interpersonal growth groups. Either being the member who enacted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Participant observation was applied, as it was deemed suitable for investigating the rich, complex, conflictual, problematic, and diverse experiences, thoughts, feelings, and activities of people (Jorgensen, 2015). Observing and recording behaviour is viewed as one of the most objective direct measurement tools available for the assessment of behaviour (Paquin et al, 2011). The conversations of the teams were recorded using a Dictaphone as they engaged in the design process.…”
Section: Data Collectionmentioning
confidence: 99%
“…Participant observation was applied, as it was deemed suitable for investigating the rich, complex, conflictual, problematic, and diverse experiences, thoughts, feelings, and activities of people (Jorgensen, 2015). Observing and recording behaviour is viewed as one of the most objective direct measurement tools available for the assessment of behaviour (Paquin et al, 2011). The conversations of the teams were recorded using a Dictaphone as they engaged in the design process.…”
Section: Data Collectionmentioning
confidence: 99%
“…These between-session processes are discussed below. Paquin et al (2011) were the first to examine attendance at the session level. In their study, if a group member was an outlier in the previous session (had either the highest or lowest number of intimate behaviors), then that group member was less likely to attend the following session.…”
Section: Between-member Predictors Of Attendancementioning
confidence: 99%
“…Both Paquin et al (2011) and Kivlighan et al (2012) examined behaviors as predictors of group member attendance. It is likely, however, that a group member's perceptions of a previous session will also affect her or his probability of attending the next session.…”
Section: Between-session Predictors Of Attendancementioning
confidence: 99%
“…Kivlighan (2011) noticed that members of interpersonal growth groups’ perceptions of the discussion session smoothness and the depth of disclosures are related to how others perceived those characteristics. Moreover, Kivlighan, Kivlighan, and Cole (2012) revealed that absenteeism during group meetings decreased when others were perceived to be committed to the discussion (although this is true only of groups whose commitment was average or below average), and future attendance is associated with partners’ intimate behaviors during the session (Paquin, Miles, & Kivlighan, 2011). Also, partners’ attachment anxiety predicted or was related to one’s assessment of the group climate (Kivlighan, Lo Coco, & Gullo, 2012).…”
Section: Modeling Partner Effects In Group Researchmentioning
confidence: 99%